(untitled) (Verse Version, 2024)
This poem, titled “Invisible Rhythm”, explores the interplay between visual art, music, and poetry, drawing inspiration from an exhibition. The poem mirrors the rhythmic and thematic elements of the exhibited works, such as Phases of the Moon and Tidings, embodying a dynamic, wave-like structure that echoes the artist’s emphasis on hidden rhythms. The author integrates the names of the artworks into the poem, reflecting their influence on its form and content. The poem’s staggered lines and varying rhyme schemes create a musical cadence, with repeated phrases like “you know it’s coming” serving as a thematic anchor. This phrase encapsulates the artist’s—and poet’s—response to existential challenges in art, particularly the threat of AI, asserting the irreplaceable value of human creativity. The poem also pays homage to literary figures like Shakespeare and Du Fu, weaving intertextual references into its meditation on art, transience, and resilience. Central to the poem is the concept of “invisible rhythm”—a subtle, deeply personal pulse underlying artistic creation, perceptible only through attentive engagement. The poet’s deliberate use of form, sound, and imagery reflects this rhythm, inviting readers to uncover layers of meaning beyond surface observation. Ultimately, the poem celebrates the enduring power of human expression, transcending technological and temporal challenges.